Prognostication with point-of-care echocardiography during cardiac arrest: A systematic review. (July 2020) - ; Andersen, Lars W.; Böttiger, Bernd W.; Callaway, Clifton W.; Deakin, Charles D.; Donnino, Michael; Hsu, Cindy H.; Morley, Peter T.; Morrison, Laurie J.; Neumar, Robert W.; Nolan, Jerry P.; Paiva, Edison F.; et al.
Abstract: Aim: To conduct a prognostic factor systematic review on point-of-care echocardiography during cardiac arrest to predict clinical outcomes in adults with non-traumatic cardiac arrest in any setting. Methods: We conducted this review per PRISMA guidelines and registered with PROSPERO (ID pending). We searched Medline, EMBASE, Web of Science, CINAHL, and the Cochrane Library on September 6, 2019. Two investigators screened titles and abstracts, extracted data, and assessed risks of bias using the Quality in Prognosis Studies (QUIPS) template. We estimated prognostic test performance (sensitivity and specificity) and measures of association (odds ratio). Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology evaluated the certainty of evidence. Results: In total, 15 studies were included. We found wide variation across studies in the definition of 'cardiac motion' and timing of sonographic assessment. Most studies were hindered by high risks of bias from prognostic factor measurement, outcome measurement, and lack of adjustment for other prognostic factors. Ultimately, heterogeneity and risk of bias precluded meta-analyses. We tabulated ranges of prognostic test performance and measures of association for 5 different combinations of definitions of 'cardiac motion' and sonographic timing, as well as other miscellaneous sonographic findings. Overall certainty of this evidence is very low. Conclusions: The evidence for using point-of-care echocardiography as a prognostic tool for clinical outcomes during cardiac arrest is of very low certainty and is hampered by multiple risks of bias. No sonographic finding had sufficient and/or consistent sensitivity for any clinical outcome to be used as sole criterion to terminate resuscitation.